Transformasi Pembelajaran PAI Berbasis Siklus di Madrasah Tsanawiyah: Cyclical Transformation of Islamic Education Learning in Madrasah - Purba, Alvira Asri Br; Salminawati, Salminawati; Dahlan, Zaini (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Islamic Religious Education learning faces challenges in responding to digital-era demands and shifting student expectations toward more participatory and contextual learning processes. Specific Background: In private Madrasah Tsanawiyah across Deli Serdang Regency, learning practices show variability in pedagogical approaches, assessment, and institutional support. Knowledge Gap: Existing studies have not sufficiently explained how learning transformation occurs across different institutional contexts nor produced an integrative conceptual model based on multi-site analysis. Aims: This study aims to analyze actual learning conditions, identify forms of transformation, examine supporting and inhibiting factors, and formulate a cross-site conceptual model of learning transformation. Results: Findings indicate that transformation occurs gradually through revisions of instructional documents, a shift from teacher-centered to student-centered learning, implementation of formative assessment, and continuous reflection and feedback practices. The process is influenced by teacher pedagogical competence, digital literacy, leadership, collaborative culture, and infrastructure limitations, alongside administrative burdens and bureaucratic constraints. Novelty: The study proposes an integrative conceptual model positioning learning transformation as a dynamic cycle involving policy implementation, pedagogical practice, reflection, evaluation, and feedback across institutional systems. Implications: Sustainable transformation depends on reconstructing teachers’ professional paradigms and strengthening institutional support systems rather than relying solely on administrative adjustments.